Combined use of platelet-rich plasma and autologous bone grafts in the treatment of long bone defects in mini-pigs - Hakimi, M.; Jungbluth, Pascal; Sager, M.; Herten, Monika; Becker, J.; Windolf, J.; Wild, M.; Betsch, Marcel (Injury-International Journal of the Care of the Injured, 2010)
The use of platelet-rich plasma (PRP) for improving of bone defect healing is discussed controversially. The aim of this study was to assess the effect of PRP in combination with autologous cancellous graft on bone defect healing in a critical metaphyseal long bone defect. A critical size defect in the tibial metaphysis of 16 mini-pigs was filled either with autologous cancellous graft as control group or with autologous cancellous graft combined with autologous PRP. Compared to native blood platelets were enriched about 4.9-fold in the PRP. After 6 weeks, the specimens were assessed by X-ray and histological evaluation. Histomorphometrical analysis revealed that the area of new bone was significantly higher in the PRP group concerning the central area of the defect zone (p < 0.02) as well as the cortical defect zone (p<0.01). All defects showed substantial new bone formation, but only defects of the PRP group regenerated entirely. The PRP group was superior to the control group even in the semi-quantitative assessment of the osseous bridging in both observed areas of the defect. Within the limits of the present study it could be demonstrated that PRP combined with autologous cancellous graft leads to a significantly better bone regeneration compared to isolated application of autologous cancellous graft in an in vivo critical size defect on load-bearing long bones of mini-pigs. © 2009 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Animal model; Bone defect; Bone healing; Growth factors; Mini-pig; Platelet-rich plasma